Global climate hazard indices: heat, drought, flood and compound - CGIAR, focus Climate Security (2024)
This dataset contains raster files of climate hazard indices at a 0.7° spatial resolution, globally. Climate hazards consist of (1) heat hazard, (2) flood hazard, (3) drought hazard, (4) compound hazard which takes into account the co-occurring effects of heat, flood and drought. The climate hazards are given for a baseline period (spanning 1981 to 2010), and a near-term future period (2020 to 2040).